KOBIlerin Finansmanında Borsalar - Selim Soydemir (Turkish Economic Association, 2012)
– Small-Medium Sized Companies(SMEs) are very important in the perspectives of employment, innovation, production and as well as exportation. But as opposed to their importance, they have faced a big problem to finance investments known as financing capabilities. Since it is not easy for them to penetrate in financial markets, it is especially needed to create new ways and instruments to them to finance themselves. One way in this perspective is securities' markets. In those markets they finance themselves through issuing securities such as shares and bonds. To sell securities to the public they must supply sufficient and efficient information (public disclosure) to the existing and potential investors. On the other hand, those markets are very much in need of liquid secondary markets, stock exchanges and organized secondary markets such as over-the-counter markets. In this article besides financing needs and problems of those SMEs, social capital and Basel II issues are also examined for the SMEs and as a result of those role and importance of Stock Exchanges for the SMEs are discussed in this perspectives.
Keywords: 330; Securities Markets; Social Capital; Small and Medium Size Companies; Small and Medium Size Companies' Finance; Basel II and Stock Exchanges for SMEs